Do you read me? Speech acts, expressive behaviour and states of mind in rape cases - Deamer, Felicity (International Journal of Speech, Language and the Law, 2023)
This paper argues that there are three separable but related dimensions that are important to the legal notion of consent. One is a consenting state of mind, the ‘going along with’ a plan of action, which may or may not be communicated or even reflected upon, but which certainly can be. A second is displaying behaviour which reveals or is an expression of consenting. Another is intentionally communicating consent. I illustrate how the communicative act is often vitally important as evidence of an underlying consenting state, but the underlying consenting state has to be postulated and brought to the fore since consensual actions (e.g. sexual intercourse) can, and more often than not do, take place without the communicative acts, and the communicative acts might for various reasons be made in the absence of the genuinely consenting state of mind. The arguments I put forward offer a reframing of cases in which an apparent intentional communication of consent was treated as consent, rather than as a piece of evidence which may or may not be indicative of a consenting state of mind. This paper emphasises that we must not allow the importance of something as evidential to eclipse the underlying phenomenon, which is itself, however hard to access otherwise, the thing of primary legal importance.